ON THE ISSUE OF THE USE OF ROLLER-COMPACTED CEMENT-CONCRETE MIXTURES FOR CONSTRUCTION OF ROAD PAVEMENTS - Bugaevsky, S. A.; Korzun, S. N.; Vinnikov, A. V.; Semyonenko, V. S.; Bugaevsky, M. S. (Харьковский национальный автомобильно-дорожный университет, 2018)
Problem. At present, on the existing roads of Ukraine the construction of road pavement does not meet the requirements for durability and load-carrying capacity, because of constant in-crease in traffic intensity, the emergence of new types of vehicles with increased axle loads and uncontrolled transport overload. The widespread use of roller-compacted cement mixes (RCC mixes) in the construction of road pavements for highways will solve these problems. Goal. The aim of the work is to study the effect of the components of a rigid cement-concrete mixture on the physical and mechanical properties of concrete, as well as the industrial introduction of the technology of RCC in Kharkiv. Methods. The methods for assessing RCC characteristics allow to carry out all necessary research on the basis of existing regulations in Ukraine. Results. As a result of the studies carried out, compositions of RCC mixtures on local materials with compres-sive strengths of 60 MPa were obtained, with a bending strength of more than 4.5 MPa, density of 2420 kg/m3 and frost resistance of F200. Novelty. The scientific novelty of the construction works is in the selection of the compositions of RCC mixes by applying high-quality cement, fine sand, two (or three) fractions of rubble, mineral additives, complex additives and nonmetallic fibers, which leads to an increase in the density and strength of the RCC, and also increases the durability of the cement concrete coatings compacted. Practical value. Laboratory research and selection of cement-concrete mixes for production of RCC used in the construction of road pavements were carried out to prove the aims of the work, as well as industrial introduction of the technology of RCC mortar has been carried out by laying the road section on the territory of the enterprise in Kharkiv city.
ДО ПИТАННЯ ПРО ЗАСТОСУВАННЯ ЦЕМЕНТОБЕТОННИХ СУМІШЕЙ, ЩО УКОЧУЮТЬСЯ ДЛЯ БУДІВНИЦТВА ДОРОЖНІХ ОДЯГІВ АВТОМОБІЛЬНИХ ДОРІГ
К ВОПРОСУ ОБ ИСПОЛЬЗОВАНИИ УКАТЫВАЕМЫХ ЦЕМЕНТОБЕТОННЫХ СМЕСЕЙ ДЛЯ СТРОИТЕЛЬСТВА ДОРОЖНЫХ ОДЕЖД АВТОМОБИЛЬНЫХ ДОРОГ
Keywords: composition of cement-concrete mixture; stiffness of cement-concrete mixture; roller-compacted cement concrete mix (RCC mix); compressive strength; tensile strength at bending; склад цементобетонної суміші; жорсткість цементобетонної суміші; цементобетон; що укочується; міцність на стиск; міцність на розтяг при згині; состав цементобетонной смеси; укатываемый цементобетон; прочность на сжатие; прочность на растяжение при изгибе; 693.5:625.7/.8